Agricultural research in the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A workshop on the planning and management of agricultural research in the South Pacific was held at the Alafua Campus of the University of South Pacific in Western Samoa from 5 to 16 October 1987. It was jointly organized by IRETA and ISNAR and...